Rare earth permanent magnets and their manufacturing methods and applications

The method addresses the uneven distribution of heavy rare earth elements in neodymium iron boron magnets by using Mn and controlled heat treatment, resulting in improved coercive force and mechanical properties.

JP7627721B2Active Publication Date: 2025-02-06YANTAI ZHENGHAI MAGNETIC MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023110616
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-07-06
Filing Date
2023-07-05
Publication Date
2025-02-06
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

Existing methods for manufacturing neodymium iron boron-based sintered magnets face challenges in achieving uniform distribution and high coercive force due to excessive consumption of heavy rare earth elements at the surface and reduced diffusion depth at lower temperatures, leading to a significant difference in coercive force between the magnet surface and core.

Method used

A manufacturing method involving a diffusion source with Mn and heavy rare earth elements, controlled heat treatment, and a hypoxia process to reduce oxygen content, ensuring even distribution and improved diffusion depth, thereby reducing the coercive force difference between the surface and core.

Benefits of technology

The method enhances the uniformity of heavy rare earth distribution, improves coercive force, and increases the mechanical properties of the magnets, particularly in motors, by optimizing the diffusion process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627721000001
    Figure 0007627721000001
  • Figure 0007627721000002
    Figure 0007627721000002
Patent Text Reader

Abstract

To provide a permanent magnet.SOLUTION: A permanent magnet includes a main phase structure of R2T14B crystal grain. R is a rare earth element. T is a transition metal including at least Mn, Fe, and optionally Co. B is boron. The permanent magnet further includes Mn and a heavy rare earth element diffused and distributed in a grain boundary. The heavy rare earth element is at least one selected from Dy, Ho, and Tb. In a rare-earth permanent magnet manufactured by a manufacturing method of the present invention, a larger amount of the heavy rare-earth element can be diffused along the grain boundary to enter a magnet core portion, a Hcj distribution of the permanent magnet is improved, and corrosion resistance and mechanical characteristics of the permanent magnet are also improved.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of permanent magnet manufacturing, and more particularly to rare earth permanent magnets and their manufacturing methods and applications. [Background technology]

[0002] Neodymium-iron-boron sintered magnets have excellent magnetic properties and are therefore widely used, and in recent years in particular, with the spread of heavy rare earth diffusion technology, the overall magnetic properties of neodymium-iron-boron magnets have been further improved, with the sum of the magnetic energy product (MGOe) and coercive force (Hcj) now exceeding 80. However, the heavy rare earths used in diffusion technology are more expensive materials, so reducing the amount of diffused heavy rare earths is of great significance for reducing magnet manufacturing costs. At present, the research of improving magnet performance by adding diffusion assistants (i.e., complex diffusion) instead of traditional grain boundary diffusion has been widely studied in the industry. Many researchers have conducted corresponding analysis on the types of elements of the assistants added, which currently mainly include the following two types: (i) Elements with low melting points (for example, less than 1100℃) such as Cu, Ga, Al, Ag, etc. are added as auxiliary diffusion sources. These elements often have the effect of improving grain boundary wettability and increasing Hcj in traditional NdFeB sintered magnets. After being added as auxiliary elements of the diffusion source, it will lead to a decrease in the melting point of the diffusion source. In this case, if diffusion is performed at the traditional heavy rare earth diffusion temperature, the heavy rare earth diffusion source will melt quickly at a relatively low temperature, and the crystal grains on the magnet surface and the diffusion source will transition and fuse, causing the diffusion source elements to penetrate excessively into the crystal grains on the magnet surface, increasing the consumption of the diffusion source elements, and leading to an increase in the Hcj difference between the diffusion magnet surface and the magnet core. In addition, by lowering the diffusion temperature, the consumption of the diffusion source is reduced, but as the diffusion temperature decreases, the movement speed of the heavy rare earth elements in the grain boundary phase decreases, and the diffusion depth is greatly reduced, making it difficult to manufacture a diffusion magnet with a relatively large thickness, and therefore difficult to obtain practical beneficial effects in actual applications. (ii) When elements with high melting points (e.g., above 1600°C) such as Zr, Ti, Nb, W, etc. are added as auxiliary diffusion sources, the melting point of the diffusion source increases after adding such elements, making it difficult for the heavy rare earth diffusion source to penetrate further into the magnet quickly, and when the diffusion temperature is increased, the proportion of the liquid phase of the magnet at high temperatures increases, leading to an intensified reaction between the diffusion source and the crystal grains on the magnet surface.

[0003] Therefore, by selecting appropriate diffusion source additive elements and diffusion temperature processes, the reaction between the diffusion source and the crystal grains on the magnet surface can be reduced, and the diffusion source can penetrate further into the magnet, thereby reducing the Hcj difference between the magnet surface and core, and improving the utilization rate and diffusion depth of heavy rare earths. This has become a technical problem that needs to be solved as soon as possible. Summary of the Invention

[0004] In order to solve the above problems, the present invention provides the following technical solutions: A rare earth permanent magnet, the permanent magnet being R2T 14 The main phase structure of B crystal grains includes R is a rare earth element, T is a transition metal comprising at least Mn, Fe, and optionally Co; B is boron, The permanent magnet further comprises Mn and a heavy rare earth element diffused and distributed at grain boundaries, The heavy rare earth element is at least one selected from the group consisting of Dy, Ho, and Tb.

[0005] According to an embodiment of the present invention, said R is at least one selected from Nd, and optionally Pr, Dy, Tb, Ho, Ce, Gd.

[0006] According to an embodiment of the present invention, the permanent magnet further includes M.

[0007] Preferably, M is at least one selected from aluminum (Al), titanium (Ti), copper (Cu), gallium (Ga), zirconium (Zr), and niobium (Nb).

[0008] According to an embodiment of the present invention, the contents of R, T, B, and M in the permanent magnet are not particularly limited and may be selected from those known in the art. Illustratively, the weight percentage of M is 0≦M≦5%.

[0009] According to an embodiment of the present invention, the Mn content at the surface of the permanent magnet is x1, the heavy rare earth content at the surface is y1, the Mn content at a location 500 μm away from the surface is x2, and the heavy rare earth content at a location 500 μm away from the surface is y2, where x1>x2 and y1>y2. In the present invention, the Mn content refers to the total mass of Mn in the main phase structure and grain boundaries. In the present invention, the Mn content at the surface of the permanent magnet refers to the Mn content close to the surface of the permanent magnet, for example, the Mn content within 10 μm from the surface of the permanent magnet.

[0010] According to an embodiment of the present invention, the coercive force at a surface portion of the permanent magnet is z1, and the coercive force at a core portion of the permanent magnet is z2, where z1>z2. In the present invention, the coercive force at a surface portion of the permanent magnet refers to the coercive force close to the surface of the permanent magnet, for example, the coercive force within 1 mm from the surface of the permanent magnet. In the present invention, the core portion of the permanent magnet refers to the geometric center of the permanent magnet.

[0011] According to an embodiment of the present invention, the thickness of the permanent magnet is m. In the present invention, the thickness of the permanent magnet refers to the length value along any diffusion direction of the permanent magnet, and may be, for example, the length value in the orientation direction of the permanent magnet, the length value in the length direction, or the length value in the width direction.

[0012] Preferably, the thickness of the permanent magnet is m≦15 mm, for example 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm.

[0013] According to an embodiment of the present invention, the permanent magnet satisfies the following formulas (1) and (2): x1 / x2≧y1 / y2 (1) [2*x1 / x2 -(z1-z2) / 2 / m]≧0 (2)

[0014] The present inventors have discovered that the compound represented by the formula (1)and It was found that when (2) is not satisfied, the Hcj difference z1-z2 between the surface and core of the permanent magnet is too large.

[0015] According to an embodiment of the present invention, the oxygen content of the rare earth permanent magnet is 2000 ppm or less. In the present invention, by using a low-oxygen process to control the oxygen content of the rare earth permanent magnet to 2000 ppm or less, it is possible to effectively reduce the formation of R oxides (e.g., neodymium oxide) in the grain boundaries and grain boundary triple point regions, improve the wettability of the grain boundaries of the permanent magnet, improve the continuity of the grain boundaries, and thus improve the diffusion depth of the heavy rare earth elements in the permanent magnet and the coercive force of the permanent magnet.

[0016] According to an embodiment of the present invention, the permanent magnet is obtained by disposing a diffusion source on the surface of a base body of a neodymium-iron-boron magnet and then performing a diffusion heat treatment.

[0017] Preferably, the oxygen content of the NdFeB magnet substrate is 2000 ppm or less. The inventors have found that if the oxygen content of the NdFeB magnet substrate is too high, the effect of the diffusion heat treatment is poor.

[0018] Preferably, the diffusion source contains at least Mn and heavy rare earths, and the Mn content is 20%wt or less, preferably 0.1wt% to 20wt%, for example, 0.1wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33wt%, 34wt%, 35wt%, 36 The inventors have found that if the Mn content in the diffusion source exceeds 20%wt, the excessive Mn reduces the concentration of heavy rare earths in the diffusion source, affecting diffusion efficiency, and if the Mn content is too little, the heavy rare earth content in localized areas of the substrate of the NdFeB magnet is too high, causing a reaction between the heavy rare earths and the crystal grains on the substrate surface to proceed, reducing the effective diffusion depth and increasing the difference in coercivity between the interior and surface of the magnet.

[0019] According to an embodiment of the present invention, the diffusion heat treatment includes at least two heat treatment stages.

[0020] Preferably, the heat treatment includes first carrying out a first stage heat treatment and then carrying out a second stage heat treatment.

[0021] Further, the conditions of the first-stage heat treatment include that the temperature of the first-stage heat treatment is 800°C to 1000°C, for example, 850°C to 950°C, and is illustratively 900°C, and the time of the heat treatment is at least 3 h, for example, 3 h to 30 h, and preferably 3 h to 35 h.

[0022] Further, the conditions of the second-stage heat treatment include that the temperature of the second-stage heat treatment is 400°C to 650°C, for example, 450°C to 600°C, and for example, 400°C, 500°C, or 600°C, and the time of the heat treatment is 1 h to 15 h, for example, 2 h to 8 h, and for example, 3 h, 5 h, or 7 h.

[0023] According to an embodiment of the present invention, the base of the NdFeB magnet may be subjected to a blackening treatment before the diffusion source is disposed. Furthermore, the blackening treatment conditions are that the magnet is blackened in an air atmosphere, the blackening temperature is 200°C to 500°C, and the blackening time is 3 min to 60 min.

[0024] According to an exemplary embodiment of the present invention, the permanent magnet is obtained by blackening the substrate of the NdFeB magnet, disposing a diffusion source on the surface of the blackened substrate, and then performing a heat treatment.

[0025] The present invention further provides a method for producing the rare earth permanent magnet, the method comprising the steps of: (1) producing a substrate for a neodymium iron boron magnet; (2) producing a diffusion source including at least Mn and a material containing a heavy rare earth element; (3) disposing the diffusion source according to step (2) on the surface of the substrate, and performing a diffusion heat treatment to obtain the rare earth magnet.

[0026] According to an embodiment of the present invention, in step (1), the substrate of the NdFeB diffused magnet may be selected from substrates known in the art, such as substrates made from raw materials known in the art.

[0027] Preferably, the base material comprises R, Fe, B, and optionally Co and / or M, with R and M having the meanings as indicated above. Illustratively, the base material comprises 27% PrNd, 4% Dy, 2% Co, 0.1% Cu, 0.1% Ga, 0.4% Al, 0.1% Zr, 1% B, and the balance Fe.

[0028] According to an embodiment of the present invention, the substrate has an oxygen content of 2000 ppm or less.

[0029] According to an embodiment of the present invention, in step (1), the method for manufacturing the NdFeB magnet base body includes smelting, milling, pressing, and sintering. In the present invention, once the base body is obtained, the smelting, milling, pressing, and sintering can all be performed by methods known in the art.

[0030] For example, the manufacturing method of the base body of the NdFeB magnet includes the steps of smelting the raw material of the NdFeB magnet, obtaining alloy flakes after melt spinning, subjecting the alloy flakes to hydrogen absorption treatment (hydrogen absorption pressure is, for example, 0.2 MPa) and jet milling to obtain alloy powder (for example, SMD=2.8 μm), orienting and pressing the alloy powder in a magnetic field, controlling the orientation magnetic field strength to 2 T, and then isostatically pressing the powder compact at 170 MPa, and vacuum sintering the powder compact (sintering temperature is, for example, 1065° C.) to obtain the base body.

[0031] According to an embodiment of the present invention, in step (1), the substrate may further be subjected to a blackening treatment, and the blackening treatment is performed under the conditions of an air atmosphere, a blackening temperature of 200° C. to 500° C., and a blackening time of 3 min to 60 min.

[0032] According to an embodiment of the present invention, in step (2), the Mn content in the diffusion source is 0.01% to 20%, preferably 0.1% to 20%, for example, 5%, 10%, or 15%.

[0033] According to an embodiment of the present invention, in step (2), the substance containing a heavy rare earth element in the diffusion source is selected from a heavy rare earth pure metal and / or a heavy rare earth compound, and is preferably a heavy rare earth pure metal.

[0034] Preferably, the heavy rare earth compound is at least one selected from a heavy rare earth fluoride, a heavy rare earth oxide, a heavy rare earth hydride, and a heavy rare earth oxyfluoride.

[0035] According to an embodiment of the present invention, the present invention does not specifically limit the manufacturing method of the diffusion source described in step (2) as long as the diffusion source is obtained. Exemplarily, the manufacturing method of the diffusion source includes separately manufacturing a diffusion source containing Mn and a diffusion source containing a heavy rare earth element, and further uniformly mixing the two to obtain the diffusion source. Exemplarily, the manufacturing method of the diffusion source includes melting and casting an alloy containing Mn and a heavy rare earth element to obtain the diffusion source.

[0036] According to an embodiment of the present invention, in step (3), the disposition can be performed by disposing the diffusion source on the surface of the substrate by at least one method selected from methods known in the art, such as thermal spraying, vapor deposition, coating, magnetron sputtering, embedding, printing, etc. Exemplarily, the disposition method includes disposing a powder containing a heavy rare earth and Mn on the substrate surface of the magnet by coating. Exemplarily, the disposition method includes disposing an alloy containing a heavy rare earth and Mn on the substrate surface of the magnet by magnetron sputtering.

[0037] According to an embodiment of the present invention, in step (3), the diffusion heat treatment is performed in a vacuum or an inert gas atmosphere.

[0038] According to an embodiment of the present invention, in step (3), the diffusion heat treatment can be carried out using methods known in the art.

[0039] According to an embodiment of the present invention, in step (3), the diffusion heat treatment includes at least two heat treatment stages.

[0040] Preferably, the diffusion heat treatment includes first carrying out a first stage heat treatment and then carrying out a second stage heat treatment.

[0041] Further, the conditions of the first stage heat treatment are that the temperature of the first stage heat treatment is 800° C. to 1000° C., for example, 850° C. to 950° C., and for example, 900° C., and the heat treatment time is at least 3 hours, for example, 3 hours to 30 hours. h, preferably 3 h to 35 h.

[0042] Further, the conditions of the second-stage heat treatment include that the temperature of the second-stage heat treatment is 400°C to 650°C, for example, 450°C to 600°C, and for example, 400°C, 500°C, or 600°C, and the time of the heat treatment is 1 h to 10 h, for example, 2 h to 8 h, and for example, 3 h, 5 h, or 7 h.

[0043] According to an exemplary embodiment of the present invention, the manufacturing method includes: (1') producing a substrate for a neodymium-iron-boron magnet and subjecting the substrate to a blackening treatment; (2') producing a diffusion source containing at least Mn and a material containing a heavy rare earth element, or optionally containing or not containing M; (3') disposing the diffusion source described in step (2') on the surface of the base body blackened in step (1') and performing a diffusion heat treatment, and then obtaining the rare earth magnet.

[0044] As a result of intensive research by the inventors to solve the above-mentioned problems, they have found that when a rare earth permanent magnet is manufactured using the above-mentioned manufacturing method, particularly after a diffusion source is placed in the base of a permanent neodymium iron boron magnet and diffusion heat treatment is performed, heavy rare earth elements diffuse from the surface of the base of the permanent neodymium iron boron magnet into the base of the permanent neodymium iron boron magnet, and a rare earth permanent magnet that satisfies the above formulas (1) and (2) can be obtained, the enrichment of heavy rare earth elements on the surface is greatly reduced, and more heavy rare earth elements are diffused evenly inside the magnet, the increase in coercivity of the diffused magnet is improved, and the difference in coercivity between the surface of the permanent magnet and the core portion is reduced. This is because during the diffusion process, the degree of reaction between the diffusion source and the main phase crystal grains on the surface of the NdFeB magnet base is reduced; that is, under the same conditions, more heavy rare earth elements diffuse along the grain boundaries and penetrate into the interior of the NdFeB magnet base without reacting with the crystal grains on the surface of the base themselves, so the utilization rate of heavy rare earth elements in the diffusion process is significantly improved and the heavy rare earth enrichment situation at the surface of the permanent magnet obtained after diffusion is reduced, and therefore the Hcj difference between the surface and core of the rare earth permanent magnet of the present invention is reduced.

[0045] The inventors have found that if the diffusion temperature during the diffusion heat treatment is too low, the diffusion rate of the diffusion source within the base of the neodymium iron boron magnet decreases, affecting the diffusion efficiency; on the other hand, if the diffusion temperature during the diffusion heat treatment is too high, the crystal grains form an excessive liquid phase at high temperature, the reaction between this liquid phase and the diffusion source progresses, and the heavy rare earth diffusion source is unable to diffuse sufficiently to penetrate into the core part of the base of the neodymium iron boron magnet, and the difference in coercive force between the interior and surface of the permanent magnet increases, affecting the use of the permanent magnet in a motor.

[0046] It is known in the art that the diffusion process of NdFeB magnets includes dissolving the diffusion source, reacting the diffusion source with the crystal grains and grain boundaries of the magnet, and diffusing the diffusion source along the grain boundaries to penetrate into the base of the NdFeB magnet. Meanwhile, the inventors have found through experiments that Mn is added to the heavy rare earth diffusion source, and the melting point of Mn is 1244°C, which is relatively close to the melting points of heavy rare earths (for example, the melting point of Tb is 1172°C, and the melting point of Dy is 1412°C), and when the content of Mn in the diffusion source is 0 wt% to 20 wt%, the melting point of the composite diffusion source is still close to the original heavy rare earth, and under this condition, the diffusion temperature of the composite diffusion source can be close to the diffusion temperature of the heavy rare earth diffusion source, so there is no problem of transition melting of the grain boundary phase due to the diffusion temperature being too high, or the reduction in the diffusion rate of the heavy rare earth element due to the diffusion temperature being too low. In addition, by introducing Mn into the diffusion source in the diffusion process, the heavy rare earth content at the magnet diffusion interface can be relatively reduced, which prevents the heavy rare earth from reacting with the main phase crystal grains due to the supersaturated diffusion on the substrate surface of the NdFeB magnet in a short time, and thus preventing the formation of an inverted core-shell structure, and the heavy rare earth in the diffusion source is consumed in large quantities on the substrate surface of the NdFeB magnet, and cannot successfully and effectively diffuse along the grain boundaries to enter the magnet. It should be understood by those in the art that the diffusion temperature refers to the temperature during the diffusion heat treatment.

[0047] The inventors further found that the blackening process slows down the reaction between the crystal grains on the surface of the NdFeB magnet base and the diffusion source, allowing more diffusion sources to penetrate into the core of the NdFeB magnet base, and reduces the difference in coercive force between the permanent magnet surface and the core. The inventors found that if the blackening temperature is too high or the blackening time is too long, the crystal grains on the surface of the NdFeB magnet base are excessively oxidized, reducing the remanence of the NdFeB magnet base, while if the blackening temperature is too low or the blackening time is too short, the crystal grains on the surface of the NdFeB magnet base are not sufficiently oxidized, causing some crystal grains to react quickly with the diffusion source.

[0048] In addition, the present invention improves the heavy rare earth distribution and Hcj distribution of the permanent magnet by disposing a diffusion source on the substrate surface of the NdFeB magnet and performing a diffusion heat treatment, and also has a certain effect on the corrosion resistance and mechanical properties of the permanent magnet. This is mainly because when diffusing using the diffusion source of the present invention, the heavy rare earth can be more uniformly distributed within the magnet, especially within the magnet surface and magnet core area, so that the consistency of the magnet composition and structure along the diffusion direction is improved.

[0049] The present invention further provides a rare earth permanent magnet produced by the above-mentioned production method.

[0050] The present invention further provides an application of the rare earth permanent magnet, preferably for use in a motor. Effect of the Invention

[0051] Rare earth permanent magnets produced by the manufacturing method of the present invention allow a larger amount of heavy rare earth elements to diffuse along the grain boundaries and penetrate into the magnet core, improving the Hcj distribution of the permanent magnet as well as the corrosion resistance and mechanical properties of the permanent magnet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0052] The technical solution of the present invention will be described in more detail below with reference to specific examples. It should be understood that the following examples are merely illustrative and explanatory of the present invention and should not be construed as limiting the scope of the claims of the present invention. Any technology realized based on the above content of the present invention is included in the scope of the claims of the present invention.

[0053] Unless otherwise specified, all materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0054] In the following examples, magnets at different positions after diffusion treatment were used as test samples and the following tests were performed:

[0055] 1. Magnetic property test: Standard samples of 1 mm-1 mm-1 mm were cut on the surface and at the geometric center of the magnet after diffusion, and the magnetic properties were measured using a pulsed magnetic field magnetometer (PFM).

[0056] 2. Composition test: After diffusion, the magnet was divided into two parts evenly in the diffusion direction, and the Mn and heavy rare earth contents at the surface and center of the permanent magnet were measured using an X-ray fluorescence analyzer (XRF). The Mn content at the surface of the permanent magnet was recorded as x1, the heavy rare earth content as y1, the Mn content from the surface of the permanent magnet to 500 μm inside the magnet was recorded as x2, and the heavy rare earth content as y2.

[0057] 3. Impact absorption energy test: After diffusion, the samples (size: approximately 55 mm-10 mm-6 mm) were measured for impact absorption energy five times using an impact tester, and the average value was calculated.

[0058] Example 1 The manufacturing method of rare earth permanent magnets is as follows:

[0059] (1) A neodymium-iron-boron sintered magnet substrate was manufactured: The raw material of the neodymium iron boron based sintered permanent magnet by weight percentage includes 27% PrNd, 4% Dy, 2% Co, 0.1% Cu, 0.1% Ga, 0.4% Al, 0.1% Zr, 1% B, and the balance is Fe. The raw material was produced into alloy flakes by melt spinning.

[0060] The obtained rapidly solidified flakes were subjected to hydrogen absorption treatment, and the hydrogen absorption pressure was 0.2 MPa. Then, jet milling was performed to obtain powder with SMD=2.8μm. An antioxidant fatty acid ester, which accounts for 0.05 wt% of the total amount of raw materials, was added and mixed uniformly to obtain alloy fine powder. The alloy fine powder was oriented and pressed in a magnetic field, and the oriented magnetic field strength was controlled to 2 T. Then, a green compact was obtained through isostatic pressing at 170 MPa. The green compact was sintered by heat treatment in vacuum, and the sintering temperature was controlled to 1065℃.

[0061] The sintered green compact was machined into a substrate with dimensions of 55 mm*10 mm*6 mm, of which the dimension in the orientation direction was 6 mm, and the oxygen content of the substrate was less than 2000 ppm.

[0062] (2) A diffusion source was manufactured: Tb powder and Mn powder were mixed in a weight percentage ratio of 95%:5%, and then 1% of 4-hexylresorcinol antioxidant and 5% of ethanol were added to mix into a slurry.

[0063] (3) Diffusion source arrangement and diffusion heat treatment: The substrate of step (1) is subjected to a blackening treatment in air, the treatment temperature is 300° C., and the treatment time is 40 min; The slurry from step (2) was coated on the surface of the substrate, and a diffusion heat treatment was performed. The diffusion heat treatment process included a first-stage heat treatment at a diffusion temperature of 940°C for 30 hours, followed by a second-stage heat treatment at 500°C for 10 hours, thereby obtaining the rare earth permanent magnet of this example.

[0064] Using the test methods described above, the magnetic properties and mechanical properties of the rare earth magnet of this example were measured.

[0065] Example 2 The manufacturing method of rare earth permanent magnets is as follows:

[0066] (1) A neodymium-iron-boron sintered magnet substrate was manufactured: The raw material of the neodymium iron boron based sintered permanent magnet by weight percentage includes 27% PrNd, 4% Dy, 2% Co, 0.1% Cu, 0.1% Ga, 0.4% Al, 0.1% Zr, 1% B, and the balance is Fe. The raw material was produced into alloy flakes by melt spinning.

[0067] The obtained rapid aggregation hardThe lake was subjected to hydrogen absorption treatment, and the hydrogen absorption pressure was 0.2 MPa. Then, jet milling was performed to obtain powder with SMD = 2.8 μm. An antioxidant fatty acid ester, which accounts for 0.05 wt% of the total amount of raw materials, was added and mixed uniformly to obtain alloy fine powder. The alloy fine powder was oriented and pressed in a magnetic field, the oriented magnetic field strength was controlled to 2 T, and a powder compact was obtained through isostatic pressing at 170 MPa. The powder compact was sintered by heat treatment in vacuum, and the sintering temperature was controlled to 1065 °C.

[0068] The sintered green compact was machined into a substrate with dimensions of 55 mm*10 mm*6 mm, of which the dimension in the orientation direction was 6 mm.

[0069] (2) A diffusion source was manufactured: Tb powder and Mn powder were mixed in a weight percentage ratio of 85%:15%, and then 1% of 4-hexylresorcinol antioxidant and 5% of ethanol were added to mix into a slurry.

[0070] (3) Diffusion source arrangement and diffusion heat treatment: The substrate of step (1) was subjected to a blackening treatment in air, the treatment temperature was 300° C., and the treatment time was 40 min in an air atmosphere. The slurry from step (2) was coated on the surface of the substrate, and a diffusion heat treatment was performed. The diffusion heat treatment process included a first-stage heat treatment at a diffusion temperature of 940°C and a heat treatment time of 30 hours, followed by a second-stage heat treatment at 500°C and a heat treatment time of 10 hours, thereby obtaining the rare earth permanent magnet of this example.

[0071] The magnetic properties and mechanical properties of the permanent magnet of this example were measured using the test methods described above.

[0072] Example 3 The manufacturing method of rare earth permanent magnets is as follows:

[0073] (1) A neodymium-iron-boron sintered magnet substrate was manufactured: The raw material of the neodymium iron boron based sintered permanent magnet by weight percentage includes 27% PrNd, 4% Dy, 2% Co, 0.1% Cu, 0.1% Ga, 0.4% Al, 0.1% Zr, 1% B, and the balance is Fe. The raw material was produced into alloy flakes by melt spinning.

[0074] The obtained rapidly solidified flakes were subjected to hydrogen absorption treatment at a hydrogen absorption pressure of 0.2 MPa, followed by jet milling to obtain powder with SMD=2.8 μm, and an antioxidant fatty acid ester, which accounts for 0.05 wt% of the total amount of raw materials, was added and mixed uniformly to obtain alloy fine powder. The alloy fine powder was oriented and pressed in a magnetic field, the oriented magnetic field strength was controlled to 2 T, and a green compact was obtained through isostatic pressing at 170 MPa. The green compact was sintered by heat treatment in vacuum, and the sintering temperature was controlled to 1065°C.

[0075] The sintered green compact was machined into a substrate with dimensions of 55 mm*10 mm*6 mm, of which the dimension in the orientation direction was 6 mm.

[0076] (2) A diffusion source was prepared: Tb and Mn were placed and dissolved in a weight percentage ratio of 85%:15%, and then a diffusion source powder was prepared. The powder was mixed into a slurry by adding 1% 4-hexylresorcinol antioxidant and 5% ethanol.

[0077] (3) Diffusion source arrangement and diffusion heat treatment: The substrate of step (1) was subjected to blackening treatment in air at a treatment temperature of 300° C. for a treatment time of 40 min. The slurry from step (2) was coated on the surface of the substrate, and a diffusion heat treatment was performed. The diffusion heat treatment process included a first-stage heat treatment at a diffusion temperature of 940°C for 30 hours, followed by a second-stage heat treatment at 500°C for 10 hours, thereby obtaining the rare earth permanent magnet of this example.

[0078] The magnetic properties and mechanical properties of the permanent magnet of this example were measured using the test methods described above.

[0079] Example 4 The manufacturing method of rare earth permanent magnets is as follows:

[0080] (1) A neodymium-iron-boron sintered magnet substrate was manufactured: The raw material of the neodymium iron boron based sintered permanent magnet by weight percentage includes 27% PrNd, 4% Dy, 2% Co, 0.1% Cu, 0.1% Ga, 0.4% Al, 0.1% Zr, 1% B, and the balance is Fe. The raw material was produced into alloy flakes by melt spinning.

[0081] The obtained rapidly solidified flakes were subjected to hydrogen absorption treatment at a hydrogen absorption pressure of 0.2 MPa, followed by jet milling to obtain powder with SMD=2.8 μm, and an antioxidant fatty acid ester, which accounts for 0.05 wt% of the total amount of raw materials, was added and mixed uniformly to obtain alloy fine powder. The alloy fine powder was oriented and pressed in a magnetic field, the oriented magnetic field strength was controlled to 2 T, and a green compact was obtained through isostatic pressing at 170 MPa. The green compact was sintered by heat treatment in vacuum, and the sintering temperature was controlled to 1065°C.

[0082] The sintered green compact was machined into a substrate with dimensions of 55 mm*10 mm*6 mm, of which the dimension in the orientation direction was 6 mm.

[0083] (2) A diffusion source was manufactured: Terbium fluoride and Mn were placed and dissolved in a weight percentage ratio of 95%:5%, and then a diffusion source powder was prepared. 1% of 4-hexylresorcinol antioxidant and 5% of ethanol were added and mixed to form a slurry.

[0084] (3) Diffusion source arrangement and diffusion heat treatment: The substrate of step (1) was subjected to blackening treatment in air at a treatment temperature of 300° C. for a treatment time of 40 min. The slurry from step (2) was coated on the surface of the substrate, and a diffusion heat treatment was performed. The diffusion heat treatment process included a first-stage heat treatment at a diffusion temperature of 940°C for 30 hours, followed by a second-stage heat treatment at 500°C for 10 hours, thereby obtaining the rare earth permanent magnet of this example.

[0085] The magnetic properties and mechanical properties of the magnet of this example were measured using the test methods described above.

[0086] Example 5 The manufacturing method of this embodiment is basically the same as that of the first embodiment, except that an acid pickling process is used instead of a blackening process before arranging the diffusion source.

[0087] Comparative Example 1 The manufacturing method of this comparative example was basically the same as that of Example 1, except that the diffusion source in step (2) was 100% Tb.

[0088] Comparative Example 2 The manufacturing method of this comparative example was basically the same as that of Example 1, except that the diffusion source in step (2) was 95% Tb and 5% Al.

[0089] Comparative Example 3 The manufacturing method of this comparative example was basically the same as that of Example 1, except that the diffusion source in step (2) was 95% Tb and 5% Ti.

[0090] Comparative Example 4 The manufacturing method of this comparative example was basically the same as that of Example 1, except that the diffusion source in step (2) was 75% Tb and 25% Mn.

[0091] Comparative Example 5 The manufacturing method of this comparative example was basically the same as that of Example 1, except that the diffusion source in step (2) was 95% terbium fluoride and 5% Al.

[0092] Comparative Example 6 The manufacturing method of this comparative example was basically the same as that of Example 1, except that the diffusion source in step (2) was 90% terbium fluoride, 5% Mn, and 5% Al.

[0093] Comparative Example 7 The manufacturing method of this comparative example was basically the same as that of Example 1, except that in step (1), the raw materials for the neodymium iron boron based sintered permanent magnet included 27% PrNd, 4% Dy, 2% Co, 0.1% Cu, 0.1% Ga, 0.4% Al, 0.1% Zr, 1% B, 0.2% Mn, and the remainder was Fe.

[0094] Table 1 is a summary of the distribution of Mn and Tb elements at different positions in the permanent magnets of the examples and comparative examples, including whether or not the Mn and Tb contents at the surface and at a position 500 μm away from the surface satisfy formula (1).

[0095] [Table 1]

[0096] Table 2 summarizes the surface coercivity, core coercivity, and magnetic properties of the surface and core of the permanent magnets of the examples and comparative examples, including the difference in coercivity, the impact absorption energy of the magnet, and other properties.

[0097] [Table 2]

[0098] From the above, it is clear from Tables 1 and 2 that in Examples 1 to 5, by introducing an appropriate amount of Mn into the diffusion source, the difference y1 / y2 in the heavy rare earth concentration in the rare earth permanent magnet produced by the present invention is further reduced, the uniformity of the magnetic properties of the magnet is improved, the difference z1-z2 in coercivity between the magnet surface and core is further reduced, and the impact toughness (shock absorption energy) of the magnet is also improved.

[0099] As can be seen by comparing Examples 1 and 5, since no blackening treatment is performed before arranging the diffusion sources, the reaction between the crystal grains and grain boundaries on the surface of the substrate and the diffusion sources is relatively fast, and as a result, the diffusion sources that penetrate into the interior of the substrate are relatively reduced, resulting in a slight decrease in the uniformity of the permanent magnets compared to Example 1.

[0100] As can be seen by comparing Examples 1 and 4, when terbium fluoride is used as the diffusion source, the uniformity of the permanent magnet is slightly reduced.

[0101] As can be seen from Comparative Examples 1 and 4, when the diffusion source does not contain Mn or when the Mn content exceeds 20%, the difference in coercivity between the surface layer and the core of the permanent magnet becomes large, and the uniformity of the permanent magnet deteriorates.

[0102] As can be seen from Comparative Examples 2, 5, and 6, the diffusion source contains Al element, which has a lower melting point, so the crystal grains on the surface of the magnet react excessively with the diffusion source, forming an inverted core-shell structure and reducing the coercive force of the magnet surface.

[0103] As can be seen from Comparative Example 3, when the diffusion source contains Ti element, which has a high melting point, it becomes difficult for the heavy rare earth elements to diffuse effectively and penetrate into the interior of the magnet, reducing the coercive force of the core of the magnet and increasing the difference between the inside and outside.

[0104] In Comparative Example 7, Mn was added to the diffusion base material, the Mn was uniformly distributed within the permanent magnet, and no Mn concentration gradient existed within the permanent magnet. Although a diffusion process was performed, the diffusion effect was inferior to that of Example 1.

[0105] The exemplary embodiments of the present invention have been described above. However, the scope of the claims of the present application is not limited to the above-mentioned embodiments. Any modifications, equivalent replacements, improvements, etc. made within the scope of the spirit and principles of the present invention should be included within the scope of the claims of the present invention.

Claims

1. A rare earth permanent magnet, the permanent magnet being 2 T 14 The main phase structure of B crystal grains includes R is selected from Nd, and may further include or exclude at least one selected from Pr, Dy, Tb, Ho, Ce, and Gd; T includes at least Mn and Fe, and may or may not include transition metals including Co; B is boron, The permanent magnet further comprises Mn and a heavy rare earth element diffused and distributed at grain boundaries, The heavy rare earth element is at least one selected from Dy, Ho, and Tb, the Mn content at a surface portion of the permanent magnet is x1, the heavy rare earth content at the surface portion is y1, the Mn content at a portion 500 μm away from the surface is x2, and the heavy rare earth content at a portion 500 μm away from the surface is y2, where x1>x2 and y1>y2; The coercive force at a surface portion of the permanent magnet is z1, the coercive force at a core portion of the permanent magnet is z2, and z1>z2; The thickness of the permanent magnet is m; The permanent magnet satisfies the following formulas (1) and (2): x1 / x2≧y1 / y2 (1) [2*x1 / x2 -(z1-z2) / 2 / m]≧0 (2) A rare earth permanent magnet.

2. The permanent magnet further includes M, M is at least one selected from aluminum (Al), titanium (Ti), copper (Cu), gallium (Ga), zirconium (Zr) and niobium (Nb); 2. The rare earth permanent magnet according to claim 1 .

3. The thickness of the permanent magnet is m≦15 mm, The rare earth permanent magnet has an oxygen content of 2000 ppm or less.

3. The rare earth permanent magnet according to claim 1 or 2.

4. A method for producing a rare earth permanent magnet according to claim 1, comprising the steps of: (1) A step of producing a substrate of a neodymium-iron-boron magnet, the raw material of the substrate containing R, Fe and B, and further containing or not containing Co, M or both; (2) preparing a diffusion source including at least Mn and a material containing a heavy rare earth element; (3) disposing the diffusion source according to step (2) on the surface of the substrate, and performing a diffusion heat treatment to obtain the rare earth permanent magnet; A manufacturing method comprising the steps of:

5. The oxygen content of the substrate of the neodymium-iron-boron magnet is 2000 ppm or less, 5. The method according to claim 4, wherein the diffusion source contains at least Mn and a heavy rare earth, the Mn content of which is 20% by weight or less.

6. The manufacturing method described in claim 5, wherein the Mn content is 0.1 wt% to 20 wt%.

7. In step (1), the method for producing the substrate of the neodymium-iron-boron magnet includes smelting, milling, pressing, and sintering, The substrate is further subjected to a blackening treatment, and the blackening treatment conditions are an air atmosphere, a blackening temperature of 200°C to 500°C, and a blackening time of 3 min to 60 min. The method according to claim 4 .

8. In step (2), the Mn content in the diffusion source is 15 wt %; In the diffusion source, the substance containing the heavy rare earth element is selected from a pure heavy rare earth metal, a compound of a heavy rare earth element, or both; The heavy rare earth compound is at least one selected from a heavy rare earth fluoride, a heavy rare earth oxide, a heavy rare earth hydride, and a heavy rare earth oxyfluoride. The method according to claim 4 .

9. In step (3), the method of disposing includes disposing the diffusion source on the surface of the substrate by at least one method selected from the group consisting of thermal spraying, vapor deposition, coating, magnetron sputtering, embedding, and printing. The method according to claim 4 .

10. In step (3), the diffusion heat treatment is performed in a vacuum or inert gas atmosphere; The diffusion heat treatment includes at least two heat treatment stages. The method according to claim 4 .

11. In step (3), the diffusion heat treatment includes first performing a first stage heat treatment and then performing a second stage heat treatment; Further, the conditions of the first-stage heat treatment include that the temperature of the first-stage heat treatment is 800° C. to 1000° C., and the heat treatment time is at least 3 hours; The conditions of the second stage heat treatment include a temperature of the second stage heat treatment of 400° C. to 650° C. and a heat treatment time of 1 h to 10 h. The method according to claim 4 .

12. A magnet comprising the rare earth permanent magnet according to claim 1. A motor characterized by:

Citation Information

Patent Citations

  • Neodymium magnet and production method therefor

    JP2012174920A

  • Method for manufacturing oriented magnet

    JP2015050427A